The Influence of ISR, Profitability, ICG on the Performance of Maqashid Syariah with Intellectual Capital as an Intervening Variable - Nafisah Rahmania; Rossje V Suryaputri (Budapest International Research and Critics University, 2022)
This study aims to show that there is a direct influence between ISR, profitability, and ICG on Intellectual Capital, a direct effect between ISR, profitability, and ICG on Maqashid Syariah Performance, and an indirect effect between ISR, profitability, and ICG on Islamic Maqashid Performance through intellectual capital as intervention variables. The sample in this study consists of 14 annual reports of Islamic banking companies in Indonesia for the 2016-2020 period, selected using the purposive sampling method. This study was tested using SEM Analysis on Smart PLS. The results of this study indicate that there is a direct influence of ISR and ICG which has an impact on the performance of Maqashid Syariah at Islamic Commercial Banks in Indonesia. And there is a direct influence of ISR and profitability has an impact on intellectual capital in Islamic Commercial Banks in Indonesia. However, ICG and ISR do not have an impact on Intellectual capital in Islamic Commercial Banks and also Intellectual capital is not able to have an impact on Sharia Maqashid Performance and the intellectual capital variable is not able to mediate the influence of ISR, profitability, and ICG on Sharia Maqashid Performance in Islamic Commercial Banks in Indonesia.